Analisis Durabilitas dan Penuaan Asbuton Pracampur dengan Variasi Lama Rendaman - Katjo, S.; Isdyanto, A. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2025)
Economic growth. Most of the existing road surface layers in Indonesia use Flexible Pavement. The fundamental problem in road construction is road damage before the planned age is reached, the factors that cause road damage can be caused by the influence of weather and water, causing asphalt aging and durability of road pavement to be damaged. The purpose of this study was to determine the Durability and Aging of Pracampur Asphalt Buton (ASBUTON) with Variations in Soaking Time by conducting experiments conducted in the laboratory through Marshall Test testing with reference to the general specifications of bina marga 2018. Short - Tern Aging (STOA) test specimens were made by heating the specimens in a loose state at 135oC for 4 hours before compaction, while Long- Tern Oven Aging (LTOA) test specimens were made by heating the specimens for 2 days at 85oC after the specimens were compacted. Durability parameters of AC-WC mixtures were observed from the residual strength index (IKS), first durability index (IDP) and second durability index (IDK). Based on the premixed asbestos mixture in the AC-WC layer, the optimum asphalt content (KAO) of 6.25% was obtained. The IKS of Normal, STOA, and LTOA specimens were 98.97%, 98.21%, and 97.69%, respectively. Furthermore, the IDP of Normal, STOA and LTOA specimens obtained r values of 0.7%, 0.11%, and 0.15%, respectively. While the IDK of Normal, STOA and LTOA test specimens obtained values of 1.53%, 2.64% and 3.41%, respectively, while the SA value of Normal, STOA and LTOA test specimens at 48 hours immersion is 98.47%, 97.36%, and 96.59%, respectively. After 48 hours of immersion at 60oC, it tends to decrease or lose strength for all test specimens and conditions.  The STOA test specimen at 48 hours of immersion experienced a significant decrease of 89.83% so that it did not meet the specifications specified in the 2018 Bina Marga Specification of 90%.